Histopathological Spectrum of Skin Neoplasm in a Tertiary care center - Basnet, Dipika; Makaju, Ramesh; Dhakal, Rachana; Gautam, Nikita; Maharjan, Prem Bahadur; Budhathoki, Arjun; Dahal, Sajana (Journal of College of Medical Sciences-Nepal, 2021)
ABSTRACT Background Skin is the largest organ in the body. An extensive range of disease can develop from various compartment of skin. Early diagnosis can help in prognosis and planning an effective management. Hence, differentiation of malignant and benign nature of the lesion is vitally important which can be achieved by histopathological examination. The objective of this study was to analyze the histomorphological spectrum of skin neoplasm received in a tertiary center. Methods This is a retrospective study done from January 2018 to December 2021 in the Department of Pathology, Dhulikhel Hospital - Kathmandu University Hospital (DH - KUH). Relevant clinical data of the patients were obtained from the histopathological records of the patient from the pathology department. Results A total of 248 cases of skin tumours were studied, out of which 194(78.2%) cases were benign and 54(21.8%) cases were malignant. The incidence of keratinocytic tumours was highest consisting of 107(43.2%) cases followed by soft tissue tumour, melanocytic tumours appendegeal tumours and hematoplymphoid tumours. Most common benign tumour was fibroepithelial polyp and malignant neoplasm was squamous cell carcinoma. The age of patient ranged from 4 to 94 years. Benign tumours were most prevalent in age group of 31-40 years and malignant neoplasm in 61-70 years. Head and neck region was the commonest site for occurrence of the skin neoplasms. Conclusions Skin tumours comprise of wide spectrum of benign and malignant lesions. Histopathological study of the skin biopsies is required for definite diagnosis and treatment.